2020
DOI: 10.5624/isd.2020.50.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiotherapy on mandibular bone: A retrospective study of digital panoramic radiographs

Abstract: Purpose: The purpose of this study was to investigate the impact of radiotherapy on mandibular bone tissue in head and neck cancer patients through an analysis of pixel intensity and fractal dimension values on digital panoramic radiographs. Materials and Methods: Thirty patients with radiographic records from before and after 3-dimensional (3D) conformational radiotherapy were selected. A single examiner carried out digital analyses of pixel intensity values and fractal dimensions, with the areas of interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…A total of 13,261 research articles were initially found in the databases after searching for all keywords. After applying the eligibility criteria and removing overlapping studies, 13,228 investigations were excluded, and a total of 33 studies 5 , 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 on the oral and maxillofacial effects of radiotherapy, as assessed by panoramic radiographs, were included. Table 1 summarizes the details of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13,261 research articles were initially found in the databases after searching for all keywords. After applying the eligibility criteria and removing overlapping studies, 13,228 investigations were excluded, and a total of 33 studies 5 , 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 on the oral and maxillofacial effects of radiotherapy, as assessed by panoramic radiographs, were included. Table 1 summarizes the details of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…The oldest study was published in 1980, 40 while the most recent ones were published in 2020. 9 10 The number of participants evaluated in the sample studied ranged from 8 37 to 176, 31 and the samples included were highly heterogeneous. Patients with head and neck cancer were often included in the investigated samples, 5 17 19 22 24 28 29 30 31 32 33 34 35 36 37 40 as were patients with hematopoietic neoplasms (such as leukemia), 12 18 23 28 33 although those with neck cancer were also studied independently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 However, few studies have demonstrated evidence of such damage through panoramic image evaluations of HNRT patients. 4 5 6 …”
Section: Discussionmentioning
confidence: 99%
“…Studies that analyzed panoramic images of HNRT patients revealed alterations such as a widened periodontal ligament space, 4 reduced thickness of the mandibular canal and cortex, 5 and decreased mean pixel intensity and fractal dimension values of the mandibular bone as side effects of ionizing irradiation on bone tissue. 6 These results suggests that research into post-radiotherapy jaw changes on imaging exams may predict ORN risk and provide insights into the need for conservative dental treatment or other preventive measures. However, the imaging profile of bone repair processes after invasive procedures, such as tooth extractions, in HNRT patients remains unknown.…”
mentioning
confidence: 88%